A Multi-Band U-Strip and SRR Loaded Slot Antenna with Circular Polarization Characteristics - Paul, P. M.; Kandasamy, K.; Sharawi, M. S. (Advanced Electromagnetics, 2020)
A compact multiband circularly polarized slot antenna is proposed here. An F-shaped microstrip feedline is used to excite the square slot antenna loaded with a U-shaped strip and a split ring resonator (SRR) to generate three circularly polarized bands at 1.5 GHz, 2.75 GHz and 3.16 GHz. A meandered slot is used in the feedline and the U-strip to improve the axial ratio bandwidth (ARBW). The meandered feedline excites the slot to produce resonance at 2.5 GHz. This resonance along with that of the F-shaped feed, loaded SRR and U-strip combine to give rise to three circularly polarized bands which can be tuned depending on the feed, SRR and U-strip dimensions. The orientation of the F-shaped feed decides the sense of polarization of the three circularly polarized bands of the proposed antenna. The proposed antenna is fabricated on a substrate of FR4 material with dimensions 50 x 50 x 1.56 mm3. The antenna is prototyped and measured in terms of impedance bandwidth, ARBW, gain and efficiency. The simulated and measured results show reasonably good agreement.